Inhibitors to Factor VIII in a Family with Mild Hemophilia: Molecular Characterization and Response to Factor VIII and Desmopressin - Santagostino, E; Gringeri, A; Tagliavacca, L; Mannucci, P M (Thrombosis and Haemostasis, 1995)
Inhibitor development in patients with mild hemophilia is a rare event. We report the occurrence of a persistent, high-responding inhibitor in two affected members of a mild hemophilia A family and discuss the therapeutic approaches employed in these patients in terms of their efficacy and effect on antibody titer. Desmopressin was an effective option for bleeding management, because endogenous factor VIII released by DDAVP was less immunogenic than exogenous factor VIII replacement, which invariably triggered anamnestic responses. Genetic analysis performed to investigate whether or not a peculiar molecular lesion accounted for this particular phenotype identified a G-A transversion at nucleotide 6507 in exon 23. This missense mutation has been already described in mild hemophilia A, but not in patients with inhibitors.